2014
DOI: 10.1038/nature12979
|View full text |Cite
|
Sign up to set email alerts
|

IL-35-producing B cells are critical regulators of immunity during autoimmune and infectious diseases

Abstract: SUMMARY B lymphocytes have critical roles as positive and negative regulators of immunity. Their inhibitory function has so far been associated primarily with interleukin (IL)-10 because B cell-derived IL-10 can protect against autoimmune disease and increase susceptibility to pathogens1,2. Here, we identify IL-35-producing B cells as novel key players in the negative regulation of immunity. Mice in which only B cells did not express IL-35 lost their ability to recover from the T cell-mediated demyelinating au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,000
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 896 publications
(1,049 citation statements)
references
References 31 publications
38
1,000
2
9
Order By: Relevance
“…7,23,43,58,59 In vitro-induced CD38 hi CD138 1 plasma cells were able to secrete large quantities of IL-10. These results are consistent with the work by Shen et al 29 and Matsumoto et al 31 who showed that CD138 1 plasma cells and plasmablast cells were the main IL-10 producers in mice with For personal use only. on April 2, 2019. by guest www.bloodjournal.org From experimental autoimmune encephalomyelitis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…7,23,43,58,59 In vitro-induced CD38 hi CD138 1 plasma cells were able to secrete large quantities of IL-10. These results are consistent with the work by Shen et al 29 and Matsumoto et al 31 who showed that CD138 1 plasma cells and plasmablast cells were the main IL-10 producers in mice with For personal use only. on April 2, 2019. by guest www.bloodjournal.org From experimental autoimmune encephalomyelitis.…”
Section: Discussionsupporting
confidence: 83%
“…11 Recent studies have shown that the latter cell subset bears regulatory properties and may be the main IL-10-producing B-cell subset in mice. [28][29][30][31] Discrepancies in the cell surface antigens studied and a lack of consensual definitions of the subset phenotypes limit the direct comparison of human B-cell subpopulation analyses. It is generally admitted that most human memory B cells are characterized by the expression of CD27 [32][33][34][35] and that human plasmablasts display a CD20 lo CD24 2 CD27 hi CD38 hi phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent study showed that IL-35-mediated negative regulation of immune responses is not restricted to CD4 1 CD25 1 Foxp3 1 T cells. 55 Some papers have reported that microRNA-containing or Fas ligand-expressing exosomes from Tregs or other tissues could mediate effector T-cell apoptosis. [56][57][58] Taken together, CD4 1 VEGFR1 high T-cell-mediated suppression might be exerted in various ways depending on the microenvironment, so that further studies to identify soluble factor(s) responsible for the suppressive activity should be considered under various circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IL-10-producing regulatory B cells, another population of B-regulatory cells (and plasma cells) was found to express IL-35 and was able to downregulate T-cell responses. Knockout mice in which only B cells did not express IL-35 lost their ability to recover from EAE [95]. In another study, IgA + plasma cells were shown to produce TNF-α and inducible nitric oxide synthase, which enhance inflammatory responses in the local environment [96].…”
Section: B-cell Cytokines and B-cell/t-cell Interactions In Msmentioning
confidence: 99%